The associations of diuretics and laxatives use with cardiovascular mortality: an individual patient-data meta-analysis of two large cohort studies - Hoppe, Liesa Katharina; Laetsch, Dana Clarissa; Koenig, Wolfgang; Brenner, Hermann; Schöttker, Ben (Cardiovascular drugs and therapy, 2019)
To investigate the associations of diuretics overall, non-potassium-sparing diuretics in specific, and laxative use with cardiovascular mortality (CVM) in subjects with antihypertensive treatment.
Gesehen am 30.03.2020